Bioconversion of glycerol to Polyhydroxyalkanoate by halophilic bacteria isolated from mangrove soil samples - Thuoc, Doan Van; Van, Nguyen Thi (Vietnam Journal of Science and Technology, 2015)
Polyhydroxyalkanoate (PHA) is a group of biodegradable polymer, synthesize by many microorganisms. PHA provide a good fully degradable alternative to petrochemical plastics. One of the major bottlenecks in the commercial application of PHAs is their high price as compared to the conventional petroleum-based plastic materials. . A potential source for low-cost PHA production is to utilize glycerol (byproduct of biodiesel production process) as carbon source. In this study, we isolated seventeen bacteria strains, which were able to synthesize PHA from glycerol. Among them, three of the strains named VK75, VK98 and VK129 (fast growth and high PHA accumulation) were chosen for further study. They are moderately halophilic and neutrophilic bacteria, able to metabolize different nitrogen sources. Highest PHA content of 61% was obtained by strain VK75 after 30 h of cultivation in flask using KNO3 as nitrogen source. Maximum CDW of 6 g/l was obtained by strain VK75 after 30 h of cultivation in bioreactor. Futher studies are being doing to optimize condition for both cell growth and PHA accumulation by three selected strains.